Antioxidative Stress and Anti-aging Effects of Lithocarpus litseifolius folium Based on Caenorhabditis elegans Model - Huikang ZHANG; Jiabo MA; Qi SI; Zhenzhen WANG; Ruyi SHA; Jing DAI; Jianwei MAO (Shipin gongye ke-ji, 2023)
In this study, the main components of the extract of (Lithocarpus litseifolius folium extract, LLFE) were analyzed,and the anti-oxidative stress and anti-aging effects of LLFE on C.elegans were evaluated using Caenorhabditis elegans (C.elegans) as a model to explore the possible mechanisms of action.The results showed that LLFE contained 52.84±1.45 mg/g of total phenols, 380.74±15.12 mg/g of total flavonoids, 470.36±5.84 mg/g of total sugars and about 6.00% of dihydrochalcone compounds, with phloridzin 52.76±0.71 mg/g, phloretin 1.64±0.06 mg/g and trilobatin 4.88±0.01 mg/g. LLFE (0.25, 1.25 mg/mL) also significantly extended the mean lifespan of C.elegans under oxidative and heat stress conditions (P<0.05) and enhanced their own resistance to stress. After using H2O2-induced oxidative damage in C.elegans as a model, it was found that LLFE (0.05, 0.25 and 1.25 mg/mL) significantly increased the mean lifespan of C.elegans compared with the model group (P<0.05). When the LLFE concentration was 1.25 mg/mL, the total superoxide dismutase activity in C.elegans increased by 39.85% (P<0.05), catalase activity by 39.21%(P<0.05) and glutathione peroxidase activity by 66.95% (P<0.001). The accumulation of malondialdehyde and reactive oxygen species was also reduced by 66.05% (P<0.001) and 49.69% (P<0.001), respectively. This indicates that LLFE has good antioxidant effect, and then delay the process of aging.